2020
DOI: 10.3389/fmicb.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Broad and Fine Scale Variability in Bacterial Diversity and Cyanotoxin Quotas in Benthic Cyanobacterial Mats

Abstract: Benthic proliferations of Microcoleus autumnalis (basionym Phormidium autumnale) and closely related taxa are being reported with increasing frequency in streams and rivers worldwide. This species commonly produces the potent neurotoxin anatoxin, and exposure to this has resulted in animal fatalities and human health concerns. Bacterial communities within cyanobacterial assemblages can facilitate processes such as nutrient cycling and are posited to influence cyanobacterial growth and function. However, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The ordination analysis of the bacterial communities showed that Proteobacteria and Bacteroidetes were almost always the main components of the samples in all islands. These two phyla have previously been identified as pioneer species and the most predominant taxa in biofilm formation in fresh and coastal waters (Lee et al 2008;Brasell et al 2015;Thomson-Laing et al 2020). Among the cyanobacterial communities, samples from each island clustered closely with the exceptions of Moorea and Rarotonga, which formed two distinct clusters.…”
Section: Benthic Bacterial and Eukaryote Diversitymentioning
confidence: 97%
See 1 more Smart Citation
“…The ordination analysis of the bacterial communities showed that Proteobacteria and Bacteroidetes were almost always the main components of the samples in all islands. These two phyla have previously been identified as pioneer species and the most predominant taxa in biofilm formation in fresh and coastal waters (Lee et al 2008;Brasell et al 2015;Thomson-Laing et al 2020). Among the cyanobacterial communities, samples from each island clustered closely with the exceptions of Moorea and Rarotonga, which formed two distinct clusters.…”
Section: Benthic Bacterial and Eukaryote Diversitymentioning
confidence: 97%
“…Benthic cyanobacterial mats are complex microbial assemblages comprising bacteria, microalgae, eukaryotic organisms and inorganic material in addition to cyanobacteria, all of which can change across successional cycles (Brasell et al 2015). The use of metabarcoding and other genomic techniques is providing valuable insights into the composition and function of these dynamic communities in freshwater systems (e.g., Bouma-Gregson et al 2019;Tee et al 2020;Thomson-Laing et al 2020), but examples of the application to toxic benthic marine cyanobacterial research are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, those characterized by a simple trichal form stand out and include representatives of genera Geitlerinema, Heteroleibleinia, Homeothrix and Jaaginema, as well as the potentially toxic species Microcoleus autumnalis [40]. Microcoleus autumnalis is known to be a producer of anatoxins, potent neurotoxins commonly attributed to Microcoleus or Phormidium genera and considered the most widely reported toxins related to benthic mats [58]. On the other hand, two simple filamentous species show a strong preference for urban waterbodies -Jaaginema subtilissimum (for SUR) and Kamptonema chlorinum (for both UR/S and SUR).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the microbial community (dominated by Bacteroidetes and Proteobacteria) within ATX-producing Microcoleus autumnale (basionym Phormidium autumnale ) -dominated mats was also reported in two New Zealand streams concerning the variability in ATX concentration. However, the presence of various co-inhabiting organisms such as diatoms and eukaryotic algae in the mats, as well as the environmental and micro-environmental conditions, may influence the bacterial community structure as well [ 138 ]. Research regarding the effect of ATXs on the bacterial assemblage in aquatic ecosystems is still at its early stages.…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 99%